Health Information Technology - Charles Senteio; Kate Magsamen-Conrad (European Journal of Health Communication (EJHC))
Achieving health equity is an established goal of health organisations (e.g., World Health Organization). Over the last 50 years, racial/ethnic health inequities have persisted across various conditions and subgroups despite increased technology deployment, because the structural factors that drive them remain (e.g., income inequality, lack of access to care). Research at the intersection of health equity and communication shows that technology can be utilised to promote health, prevent disease, and manage illness. However, less work has satisfied the issues described in the OECD report Health at a Glance: Europe 2022, such as to improve population health outcomes and health equity. So, we conducted an umbrella review of health-communication intervention research with a technology component to detail what is known and remains unknown, and used a broad, interdisciplinary perspective to provide recommendations for practice and future research. In them, we champion culturally-sensitive approaches that elevate the role of community members in the design, testing, and implementation of theory-informed interventions, such as participatory design or community-based participatory research strategies. Doing so leverages technology while reducing risk of intervention-generated inequalities. We recommend systematic integration of community-level variables such as social determinants of health to reveal population level intervention strategies to mitigate health inequality.